MODEL ALTMAN (Z-SCORE) UNTUK MEMPREDIKSI FINANCIAL DISTRESS: PENERAPAN GOOD CORPORATE GOVERNANCE DI INDONESIA - Salsabil Faddhila Putri Setiawan; Shinta Permata Sari (Jurnal Akuntansi dan Pajak, 2024)
The Indonesia Stock Exchange (IDX) recorded that the primary consumer goods sector weakened by 7.43% until August 2021 compared to the consumer and non-primary raw goods sectors. The use of good corporate governance principles can improve company performance both in normal and post-crisis conditions. This study aims to determine the effect of board size, board independence, board of directors, and audit committee on financial distress in consumer non-cyclicals sector companies for the 2020-2022 period. This research is a type of quantitative research using secondary data, namely annual reports and audited financial statements. The sampling technique used is a purposive sampling technique with a total sample of 107 data during the 2020-2022 period. The data analysis used in this research is multiple linear regression analysis. The results showed that board size and board of directors affect financial stress. Meanwhile, the independence board and audit committee do not affect financial distress.